(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Infertility is the failure to become pregnant after 12 months of copulation without contraception . Thyroid defeat in function can caused to the: menstrual disorder, an ovulatory phase and lower fertility. This search formed to assess the importance of thyroid syndromes in infertility women and importance the autoimmunity by assessing value of TSH, T3, T4, & anti Thyroid peroxidase antibody in infertile woman comparison the consequences with women controls. The direction in this search started from March 2015 to September 2015 at Karbala Maternity Hospital, infertility unit, and some private clinics. Showed significant relation between TPO and BMI in controls and patients p –value (<0.002 ,<0.0001) respectively, and significant relation between BMI and T4 in patients and controls p-value (<0.0001) , and shows significant relation between , the relation between BMI and sex hormones shows no significant relation with LH in patients but significant in controls p-value (<0.0001) and relation with FSH was not significant in patients and controls , and relation with E2 shows significant relation in patients p-value (<0.01) but no significant in controls. This search directed to estimation the relationship between thyroid function and sex hormones with BMI. Where the height of BMI affects the body to increase TPO and T4 and affect estradiol , we recommend that women maintain the body weight within normal